Trade liberalisation and regional integration: the search for large numbers - Robinson, Sherman; Thierfelder, Karen (Wiley, 2002)
We surveyed the empirical literature using multi-country computable general equilibrium (CGE) models to analyse potential and actual regional trade agreements (RTAs). The studies indicate that these RTAs improve welfare, that trade creation greatly exceeds trade diversion,and that they are consistent with further global liberalisation. The welfare gains are bigger when models incorporate aspects of new trade theory such as increasing returns, imperfect competition, and links between trade liberalisation, total factor productivity growth, and capital accumulation." -- Authors' abstract